Key team physical and technical performance indicators indicative of team quality in the soccer Chinese super league - Yang, G.; Leicht, A. S.; Lago, C.; Gómez, M.-A. (Research in Sports Medicine, 2018)
The aim of this study was to identify the key physical and technical performance variables related to team quality in the Chinese Super League (CSL). Teams` performance variables were collected from 240 matches and analysed via analysis of variance between end-of-season-ranked groups and multinomial logistic regression. Significant physical performance differences between groups were identified for sprinting (top-ranked group vs. upper-middle-ranked group) and total distance covered without possession (upper and upper-middle-ranked groups and lower-ranked group). For technical performance, teams in the top-ranked group exhibited a significantly greater amount of possession in opponent`s half, number of entry passes in the final 1/3 of the field and the Penalty Area, and 50-50 challenges than lower-ranked teams. Finally, time of possession increased the probability of a win compared with a draw. The current study identified key performance indicators that differentiated end-season team quality within the CSL.